Does the quality of internal audit matters? A corporate governance perspective - Safa Eltyaf Abdalamer, Mohammed Hassan Sabbar, (Opción, 2019)
The prime objective of the current study is exploring the role of internal audit quality in activating the principle of corporate governance for the sample of Iraqi listed manufacturing firms via statistical research methodologies such as Logit regression and Correlation analysis. The results indicate that along with independence, it is mandatory to have a qualified person on a board committee. Similarly, the frequency of audit committee also appears in positive relation to corporate governance practices for the sample of Iraqi firm. In conclusion, the results of the study provide support with agency theory.